Marketing in Regional Apparatus: A Regional Innovation Initiative to Build Institutional Identity, Image and Reputation - Aries, Aries (Indonesian Journal of Social Science Research, 2022)
Marketing is an ideal conception that has not been much in demand and has not been seen in its application in local governance and public services in Banten Province Regional Apparatus. The main cause of this is that there are no regulations and limited education about the importance of implementing marketing in regional apparatus. So that the application of marketing in regional devices needs to be used as a regional innovation initiative as stipulated in Government Regulation No. 38 of 2017 concerning Regional Innovation. Because with marketing, regional apparatus get tangible benefits; improve performance and as an effort to build identity, image and achieve institutional reputation.